THE APPLICATION OF OKETANI MASSAGE IN INCREASING BREAST MILK PRODUCTION IN POST-CESAREAN SECTION MOTHERS - Melafilani S (Universitas Bina Bangsa Getsempena, 2024)
In post Sectio Caesarea mothers often experience problems with poor milk production. this is due to pain at the suture location which inhibits the production of prolactin and oxytoxsin which play a role in the smooth production of breast milk, to smooth breast milk production, nonpharmacological efforts are needed, namely with Breast care Oketani massage is a breast massage technique that focuses on the aerola and nipple area to stimulate the hypothalamus, adenohypophysis so that it secretes prolactin which can stimulate alveoli cells that function to make breast milk. The purpose of the case study describes the application of oketani massage in increasing breast milk production in post Sectio Caesarea mothers. The research method used is descriptive with a case study approach and data collection techniques through interviews and observations. This study was conducted with a sample size of 2 respondents with the criteria of mothers who gave birth with sectio caesarea, patients who were cooperative and willing to become respondents. This study was conducted on August 02 to August 16, 2023. The results showed that after the intervention of applying oketani massage for 3 days, breast milk production in respondent I increased from 7 ml to 85 ml and respondent II increased from 5 ml to 65 ml. Thus it can be concluded that the application of oketani massage can increase breast milk production in post Sectio Caesarea mothers. It is hoped that the community can increase the application of oketani massage as an alternative therapy in increasing breast milk production.